Past 6-Month Prevalence of IPV Victimization among Transgender and Gender-Diverse Undergraduate Students: A Brief Report - Huff, Merle (Journal of interpersonal violence, 2024)
Research has largely neglected the issue of intimate partner violence (IPV) among transgender and gender-diverse (TGD; e.g., nonbinary and genderqueer) individuals. However, existing research suggests that TGD individuals are disproportionately affected by IPV. The current study sought to explore if and how rates of IPV vary among subgroups of TGD undergraduate students and contextual factors of IPV among TGD individuals including the co-occurrence of multiple forms of IPV victimization, the type of relationship in which IPV occurred, and the gender identity of the IPV perpetrator. Participants were 280 TGD undergraduate students attending 20 medium- and large-sized residential public universities across the contiguous United States. Of the entire sample of TGD undergraduate students (N = 280), a total of 27.5% endorsed past 6-month IPV victimization (20.0% psychological, 6.1% physical, 8.9% sexual, 11.4% coercive control, and 5.7% LGBTQIA+-specific). Among only the participants who endorsed past 6-month IPV victimization (N = 77), 45.4% reported one form of IPV victimization, 26.0% two forms, 22.1% three forms, and 6.5% four forms. Further, 41.3% of TGD IPV victims were in a casual relationship, 56.0% were in a serious relationship, and 2.7% were in multiple relationship types. Finally, 55.8% of victims reported their perpetrator was a man, 22.1% a woman, and 22.1% a TGD individual. No significant differences in rates of IPV were found between TGD respondents. These data highlight the urgent need for programming efforts on college campuses that are specifically designed to prevent and address IPV among and against TGD students. Future research should evaluate universal- and population-specific risk and protective factors for IPV among TGD individuals to inform prevention and response efforts for this highly vulnerable population.